2015
DOI: 10.2500/ajra.2015.29.4198
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes on and Usage of Balloon Catheter Technology in Rhinology: A Survey of the American Rhinologic Society

Abstract: ARS members surveyed used BCT infrequently in their practices. Attitudes on the role of this technology in CRS management differed between academic and private practitioners, but, despite this, the volume of reported BCT use was the same. Surgeons are more accepting of the technology now compared with 5 years ago, and many of them believe that their use of BCT will increase in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…When evaluating the BCDs that were performed as solo procedures, 24 of 53 (45.3%) were done in the OR. This is comparable to the 54% OR rate reported in the ARS survey . It is worthy to note that CPT codes for BCD were approved in 2011, which corresponded with the beginning of the period studied.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…When evaluating the BCDs that were performed as solo procedures, 24 of 53 (45.3%) were done in the OR. This is comparable to the 54% OR rate reported in the ARS survey . It is worthy to note that CPT codes for BCD were approved in 2011, which corresponded with the beginning of the period studied.…”
Section: Discussionsupporting
confidence: 79%
“…Of these four, three are community hospitals and one is an academic medical center, and none is in the top three with regard to patient volume in the DoD. This finding is consistent with findings of the previously referenced ARS survey data, which showed a majority of providers performing only one to four BCDs per month versus <10% of providers who performed >11 BCD per month . In an extensive review of national Medicare data, Venkatraman et al found ESS rates varied five‐fold between hospital referral regions (HRRs) .…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, favorable evolution of attitudes toward BSP also may be contributing to the rise in utilization of the technology. A survey of American Rhinologic Society members showed that surgeons have become more accepting of BSP compared to 5 years prior, and several respondents predicted that their use of BSP would increase in the future …”
Section: Discussionmentioning
confidence: 99%
“…It appears that, compared with 5 years ago, rhinologists are more accepting of this method. 9 Cystic fibrosis (CF) is a disease with multiple infectious and inflammatory complications, including CRS. Two studies in this issue of AJRA address clinical and pathologic aspects of this association.…”
Section: T His Issue Of American Journal Of Rhinology Andmentioning
confidence: 99%
“…However, no single curvature or combination of curvatures reached the entirety of the maxillary sinus wall. 8 Halderman et al 9 did an on-line survey to evaluate the opinion of rhinologists regarding use of balloon catheter dilatation (BCT) in the management of paranasal sinus diseases in CRS and recurrent acute rhinosinusitis. Twenty-five percent (n ϭ 231) of the members of the American Rhinologic Society responded.…”
Section: T His Issue Of American Journal Of Rhinology Andmentioning
confidence: 99%